Medical Ozone Treatment Alleviate Blood Oxidative Stress And Pancreas Damage In an Alloxan-Induced Diabetes Model in Rats - Falih, Shaymaa; Bushra F. HASAN, (University of Thi-Qar Journal of Science, 2023)
Diabetic mellitus (DM ) is a prevalent systemic disease affecting a human and animals. The effects of diabetes are devastating and well documented. The increased production and/or ineffective scavenging of reactive oxygen species (ROS) may play a critical role in the development of diabetic complications. Therefore, it seems reasonable that antioxidants can play an important role in the improvement of diabetes. So, use medical ozone to study if it can regulate the oxidative complications of DM .The study was carried out on forty eight  albino females rats included six groups Group I (Control) : 8 female rats were  injected  IP  with  citrate buffer (0.1 M, pH 5) daily for 6 weeks ,Group II (MO ): 8 female rats were  injected  IP 1.1 mg/kg  b.w of MO daily for 6 weeks ,Group III (DM): 8 female rats induce diabetes by injection IP with  freshly prepared alloxan 150 mg/kg b.w in citrate buffer (pH 5), Group IV(DM+MO): 8 diabetic female rats were injected  IP 1.1 mg/kg  b.w of MO daily for 6 weeks,  group V(DM + Insulin): 8 diabetic female rats were injected subcutaneously 0.75 IU/100 g b.w. of Insulin daily for 6 weeks ,Group VI(DM +MO +Insulin):8diabetic female rats were injected IP 1.1 mg/kg  b.w of MO and Insulin  injected subcutaneously at a dose of 0.75 IU/100 g b.w , respectively daily for 6 weeks. experimental study parameters include  antioxidant enzymes assay and histology the study for pancreas.